Recent advances in intestinal lymphomas. Issue 1 (January 2015) - Foukas, Periklis G; de Leval, Laurence
<x xml:space="preserve">Abstract</x> A large variety of lymphoma types may develop as primary intestinal neoplasms in the small intestines or, less often, in the colorectum. Among these are a few entities such as enteropathy‐associated T‐cell lymphoma or immunoproliferative small intestinal disease that, essentially, do not arise elsewhere than in the gastrointestinal tract. In most instances the primary intestinal lymphomas belong to entities that also occur in lymph nodes or other mucosal sites, and may show some peculiar features. In the case of follicular lymphoma, important differences exist between the classical nodal cases and the intestinal cases, considered as a variant of the disease. It is likely that the local intestinal mucosal microenvironment is a determinant in influencing the pathobiological features of the disease. In this review we will present an update on the clinical, pathological and molecular features of the lymphoid neoplasms that most commonly involve the intestines, incorporating recent developments with respect to their pathobiology and classification. We will emphasize and discuss the major differential diagnostic problems encountered in practice, including the benign reactive or atypical lymphoid hyperplasias, indolent lymphoproliferative disorders of T or natural killer (NK) cells, and Epstein–Barr virus (EBV)‐related lymphoproliferations.